ANALISIS SEMIOTIKA FILM PENDEK TANPA DIALOG “PERSPEKTIF TERBALIK” (STUDI ANALISIS ROLAND BARTHES) - Lukman Al Hakim; Veny Purba (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
The film in this study did not use dialogue or conversation but instead used expressions, gestures and symbols. The purpose of this study is to determine the meaning and message of the visuals conveyed by each scene in the short film 'Reverse Perspective'. This research shows that the symbol for delivering messages in this film uses facial expressions to convey a message of the feeling of a player in it, the property in his room which indicates he is doing something repeatedly, colour grading which indicates the difference before the slash after taking drugs. The conclusion of the message conveyed in the film 'Reverse Perspective' is to think long beforehand in the decisions we choose, because when we make a wrong decision, we must be prepared to face these risks because every decision has consequences.